KUALITAS HIJAUAN KACANG PINTOI (Arachis pintoi) PADA BERBAGAI PANJANG STEK DAN DOSIS PUPUK ORGANIK CAIR - Rachmansyah, Alfi; Sumarsono, Sumarsono; Sutarno, Sutarno (Animal Agriculture Journal, 2012)
This study aims to determine the quality of the forage pintoi peanut (Arachispintoi) at various cutting length and liquid organic fertilizer (POC) is different. Thematerial used is Arachis pintoi plant, Liquid Organic Fertilizer and granules(Herbafarm). The instrument used was 5 kg capacity scales, analytical scaleselectrical capacity of 1 kg with 0.01 g accuracy, pumpkin destruction, burette, beakerglass, porcelain bowls, H2SO4, N Hexan, NaOH, MB + MR indicator, filter paper,shovel, hoes, buckets, ruler / tape measure, stationery, tape, scissors, cutter, paperlabels, plastic bag, oven, furnace and eksikator. The trials were prepared using acompletely randomized design patterned Factorial 2 x 4 with 3 replications, with thefirst factor of the length of cuttings and the second dose of liquid organic fertilizer(POC) is different. The cutting length consists of 2 segments (S1) and 3 segments(S2), while the dose of liquid fertilizer composed of 0 ml / l (P1), 5 ml / l (P2)(dosage recommendations), 10 ml / l (P3) and 15 ml / l (P4). The data obtained wereanalyzed range, when significant followed by Duncan multiple test areas (5%) todetermine differences between treatments. The results of the analysis showed that thetreatment of long-range cuttings and different doses of POC, and the interactions theyprovide no significant effect (P> 0.05) on levels of protein and fiber content of roughforage. The length of cuttings significant influence (P <0.05) the production of CrudeProtein. Production of crude protein peak obtained at treatment S2 (324,59 g) andfollowed by S1 (244,56 g).Key word: Arachis pintoi, cutting length, POC, crude protein and crude fiber